2007
DOI: 10.1177/1352458506070750
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive impairment in multiple sclerosis using the Symbol Digit Modalities Test

Abstract: Cognitive impairment is common in multiple sclerosis (MS), yet difficult to detect during routine neurologic examination. Therefore, brief screening tests that identify patients who may benefit from a more thorough assessment or treatment are needed. We investigated the utility of the Symbol Digit Modalities Test (SDMT) as a screen for cognitive dysfunction because it can be administered and scored in about 5 minutes. One hundred MS patients and 50 healthy controls, matched on demographic variables, participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
235
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(259 citation statements)
references
References 28 publications
9
235
3
7
Order By: Relevance
“…First, only 21% of patients were impaired on the SDMT, which is relatively low compared with other studies. 10,45 Second, neither the duration of MS symptoms nor the participants' level of physical disability was reported, which, therefore, could limit the ability to compare the findings with those of other studies or to interpret them in a clinical context. Future research should use very large samples (thousands of patients), fully characterized, for better representativeness of the study sample and generalizability of results instead of the relatively low number of participants currently reported in most studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, only 21% of patients were impaired on the SDMT, which is relatively low compared with other studies. 10,45 Second, neither the duration of MS symptoms nor the participants' level of physical disability was reported, which, therefore, could limit the ability to compare the findings with those of other studies or to interpret them in a clinical context. Future research should use very large samples (thousands of patients), fully characterized, for better representativeness of the study sample and generalizability of results instead of the relatively low number of participants currently reported in most studies.…”
Section: Resultsmentioning
confidence: 99%
“…Because processing speed is a primary deficit in individuals with MS, the SDMT may be a particularly good candidate for cognitive screening purposes; previous studies have found it to be effective. 10 Similar to the batteries mentioned previously herein, however, the SDMT does not provide information on real-life outcomes.…”
Section: The Cognitive Index: Composite Z Score Index Derived From Thmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained safety laboratory measures including transaminases, triglycerides, creatinine, and thyroid-stimulating hormone concentrations at each visit. We assessed cognition with the symbol digit modality test (SDMT) that is sensitive to both cognitive dysfunction in multiple sclerosis 29 and cognitive dysfunction associated with excessive anticholinergic treatment in the elderly. 30 We assessed fatigue via the multidimensional assessment of fatigue (MAF) scale.…”
Section: Discussionmentioning
confidence: 99%
“…LCLA is the best-assessed and most well validated functionally relevant psychophysical clinical trial outcome for multiple sclerosis. 26,29 This clinical effect was confounded by a learning effect observed for LCLA assessments over the course of the trial. This made detection of clinical effects of the drug more difficult.…”
Section: Discussionmentioning
confidence: 99%